Property SG - Yang, Jing (Nanyang Technological University, 2020)
Modern technology has promoted social progress, and it makes an enormous contribution to people's lives. Nowadays, people are highly associated with technology, which changes the way how people interact with society. Technology provides excellent tools and sources that make people's lives much easier and better. The mobile application (app) is one of the most powerful tools. With rapid development, more and more people enjoy the advantages that mobile apps bring to them. With the emerging mobile apps, traditional industries have changed the way the business operated dramatically. The real estate industry is one of the sectors that benefitted from mobile apps. This project aims to provide an android mobile app for the real estate industry. It helps users reduce time costs when searching for property information. Meanwhile, it also offers an excellent platform for house owners and hunters to have effective communication between them. The author spent a lot of effort and thoughts to deal with the challenges and difficulties to provide a better user experience. At meantime, there are some takeaway lessons when developing the mobile app, which the author treats as a memorable learning experience that will benefit future projects.